Alkali metal alkoxyborate ester salts; a contemporary look at old compounds - Berger, Amanda; Ibrahim, Ainee; Hales, Thomas A.; D'Angelo, A.M.; Buckley, Craig E.; Paskevicius, Mark (2024)
Research into the use of sodium tetraalkoxyborate salts for different chemical applications including synthetic catalysis, hydrogen storage, or battery applications has been investigated, however, understanding of the structural, thermal and electrochemical properties of these salts has been lacking since the 1950s and 1960s. A review of the synthesis, as well as a thorough characterization using 1H NMR, 11B NMR, 13C{1H} NMR, FTIR, XRD, in situ XRD, DSC-TGA, RGA-MS, TPPA, and EIS has newly identified polymorphic phase changes for Na[B(OMe)4], K[B(OMe)4], Li[B(OMe)4], Na[B(OEt)4], Na[B(OBu)4], and Na[B(OiBu)4]. The crystal structure of K[B(OMe)4] was also solved in I41/a (a = 22.337(2) Å, c = 7.648(3) Å, V = 3815.6(4) Å3, ρ = 1.128(1) g cm−3). Ionic conductivity of the different salts was analyzed, however it was found that the compounds with longer alkyl chains had no measurable ionic conductivity compared to the shorter chained samples, Na[B(OMe)4] and K[B(OMe)4] with 9.6 × 10−8 S cm−1 and 1.6 × 10−7 S cm−1, at 114 °C respectively.